Catgut and polyglycolic acid. An evaluation in the human stomach. - Cassie, A. B. (Royal College of Surgeons of England, 1977)
The breaking tensions of catgut and polyglycolic acid (Dexon) sutures placed within and then recovered from the human stomach were compared on each of 5 postoperative days. A substantial difference was evident in the performance of the two materials under these conditions. The extreme variability of catgut degeneration contrasted with the constant performance of polyglycolic acid.